PEMBERANTAS KEMISKINAN DAN KECUKUPAN MODAL DI DUA DIMENSI BERBEDA MELALUI MODEL APEX BPR DAN GRAMEEN BANK - Muhammad Khoirul Fuddin (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2011)
This research is based on two models of the object model of the Grameen Bank that successfully implemented in rural communities of Bangladesh and APEX BPR models have been suggested by the Central Bank of Indonesia. It is expected that these two models can be reduced poverty in Indonesia. Conclusions can be drawn from this study is that the level of poverty later in Indonesia in handling through lending activities were not able to use only one in the same way. this is because, since this type of poverty in rural and urban areas have differences. With the APEX BPR is felt more appropriate to extend credit in the urban poor Grameen Bank model is more suitable to be applied to extend credit in rural communities